Evaluation of rural comprehensive development level and obstacle factors in various countries around the world - Yiyong Chen; Ling Zhu; Jinzhao Du; Wuyang Hong (PLoS ONE, 2025)
At present, major developing countries in the world are entering a stage of rapid urbanization, and rural transformation and development are accelerating. Conducting international comparisons of rural development, evaluating and diagnose rural development levels of various countries and summarizing the advantages of rural areas in developed countries. These summaries and comparisons are important for developing countries to implement rural revitalization and promote the transformation of rural regional systems. Basing on the connotation of rural development, this study constructs an evaluation index system for rural development level worldwide. Through AHP-entropy method, TOPSIS method, obstacle model, and regression model, this study analyzes the rural comprehensive development level of 175 countries and regions and obstacle factors on the basis of statistical data from the United Nations and World Bank. Results suggest significant differences in the comprehensive development level of rural areas among countries at the global level. In addition. The comprehensive development level of rural areas exhibits definite correlations with national income level, per capita GDP, and the Human Development Index (HDI), among which it shows the weakest correlation with the level of urbanization. The main obstacle factors to rural development in various countries are agricultural mechanization level, agricultural land output rate, average per labor of cultivated land area, number of doctors per thousand, and per capita income of farmers. The factors affecting the rural development level are resource endowment, economic development level, education level, and government support for agriculture. Based on the research findings, this study proposes strategic recommendations for improving the rural comprehensive development level from the perspectives of agricultural and rural development and the living standards of farmers.